2009
DOI: 10.5194/bg-6-487-2009
|View full text |Cite
|
Sign up to set email alerts
|

Optics and remote sensing of Bahamian carbonate sediment whitings and potential relationship to wind-driven Langmuir circulation

Abstract: Abstract.Regions of milky white seas or "whitings" periodically occur to the west of Andros Island along the Great Bahama Bank where the bottom sediment consists of finegrained aragonite mud. We present measurements of inherent optical properties within a sediment whiting patch and discuss the potential for monitoring the frequency, extent, and quantity of suspended matter from ocean colour satellite imagery. Sea spectral reflectance measured in situ and remotely from space revealed highly reflective waters el… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 55 publications
5
46
1
Order By: Relevance
“…Particulate attenuation coefficients were higher at the patch reef after the storm of 17 October, when winds >10 m¨s´1 occurred. Dierssen et al [31] concluded that winds >7.35 m¨s´1 can trigger resuspension of sediments over the Bahamas Banks at depths of about 5 m. Lapointe et al [71] also proposed that winds play an important role in the dynamics of nutrients and chlorophyll concentrations by changing advection patterns in the Lower Florida Keys. Our results show high turbidity and c p conditions due to suspended sediments under these short high wind events, which are quite common in Florida during summer.…”
Section: Discussionmentioning
confidence: 99%
“…Particulate attenuation coefficients were higher at the patch reef after the storm of 17 October, when winds >10 m¨s´1 occurred. Dierssen et al [31] concluded that winds >7.35 m¨s´1 can trigger resuspension of sediments over the Bahamas Banks at depths of about 5 m. Lapointe et al [71] also proposed that winds play an important role in the dynamics of nutrients and chlorophyll concentrations by changing advection patterns in the Lower Florida Keys. Our results show high turbidity and c p conditions due to suspended sediments under these short high wind events, which are quite common in Florida during summer.…”
Section: Discussionmentioning
confidence: 99%
“…Hurricanes Edouard and Hortense introduced enough energy into a 70 m deep water column to resuspend bottom sediments over 30 m above the bottom [Chang et al, 2001]. Even lower but persistent winds can cause shallow water Langmuir "Supercells" that can serve to redistribute benthic algae and resuspend sediments off the seafloor [Gargett et al, 2004;Dierssen et al, 2009aDierssen et al, , 2009b. Once suspended, sediments can persist in the water column for several days.…”
Section: Temporal Variability In Particle Size Distributionsmentioning
confidence: 99%
“…Suspended sediments, like the aragonite mud on the Great Bahama Bank, highly backscatter light out of the water (35). The size, outer coating, and 3D structure all influence the specific backscattering properties of phytoplankton (36).…”
Section: Backscattering Propertiesmentioning
confidence: 99%